PEMBUATAN SABUN PADAT DI TKIT QURRATA A’YUN DI CIMAHI - Mutiara Putri Utami; Kenny Kencanawati; Riza Rizkiah; Dini Yulianti (LPPM IST AKPRIND Yogyakarta, 2020)
The growing population and the increasing culinary industry have resulted in the production of used cooking oil (cooking waste) in large quantities. This cooking oil if consumed many times will cause disease so that it can disturb health, but if it is thrown away into the environment it will cause environmental pollution. To overcome this, it is necessary to strive for used cooking oil to be processed into ingredients that have added value. One of the uses of used cooking oil is as raw material for making solid soap. The method used is through the safonification reaction. First some reagents needed such as Sodium Hydroxide, filtered cooking oil, fragrances and natural dyes, are put into a container, then stirred, molded, then left until the soap hardens. The results show that the formed soap meets some basic criteria of solid soap with aroma and color that is adjusted to your desire.